Pharmaceutical Contaminants Occurrence and Ecological Risk Assessment Along the Romanian Black Sea Coast - Vasile-Ion Iancu; Laura-Florentina Chiriac; Iuliana Paun; Cristina Dinu; Florinela Pirvu; Victor Cojocaru; Anda Gabriela Tenea; Ioana Antonia Cimpean (Toxics, 2025)
The work aimed to investigate the presence of pharmaceutical compounds from the anti-inflammatory class in seawater from the Romanian Black Sea coast and to assess the ecological risk of these substances on the most sensitive organisms. Using the solid-phase extraction technique (SPE) followed by liquid chromatography separation and mass spectrometry detection (LC-MS/MS) of the compounds, the concentrations of these contaminants in selected seawater samples were determined. Ibuprofen was the most commonly detected compound with a frequency of 42.9%, followed by ketoprofen at 31.0.%, diclofenac at 23.8%, and naproxen at 21.4%. The maximum concentrations of pharmaceutical products varied between 13.4 ng/L ketoprofen and 13,575 ng/L caffeine. The order of decreasing maximum concentrations of pharmaceutical compounds in the water of the Black Sea was CAF > IBU > NAP > DIC > KET. The dominant and ubiquitous compound that was determined with the maximum concentration values was caffeine. Strong correlations were observed between three compounds (naproxen: diclofenac, diclofenac: ketoprofen) suggesting the same pollution source. Through the ecological risk assessment, it was observed that both caffeine and ibuprofen can generate high ecological risks for some echinoderms, crustaceans, and fish.